(untitled) (Journal of Global Accounting, 2023)
There has been growing concerns about the decline in earnings quality reported in the financial statement of firms. This is attributed to earnings manipulations and ineffective code of corporate governance. Thus, chief executive officer engaged in various activities to maintain company’s viability in order to assure investors of their investment and to invest. This study examined the effect of chief executive officer tenure (CEOT) on earnings quality of listed Nigeria companies in the context of pre- and post-2011 code of corporate governance reforms for the period 2003 to 2018. The period 2003–2010 represent pre and 2011–2018 as post-2011 code requirement. One-hundred and sixty-nine (169) listed companies as at 31st December, 2018 formed the population of study and Taro Yemane’s formula was used to determine one hundred and nineteen (119) sample companies that were randomly selected as the sampled size. Data collected from secondary source (the publications of Nigerian Exchange Group and audited annual reports of the sampled firms between the period 2003 and 2018) were analysed on the basis of pool, fixed and random ordinary least square regression. Hausman test and Independent T-test was further carried out. The random effect result revealed that CEOT was negative and not significant on discretionary accrual of listed firms in Nigeria post-2011 than pre-2011 code reforms (β1 = -0.019914, T-Stat.= -0.2775, Prob.> (t) = 0.7814). The study concludes that increase in CEOT has led to decrease in discretionary accrual which in turn increased earnings quality. The study recommends that the regulatory bodies should increase or maintain the numbers of times the chief executive officer retained his or her position in the subsequent amendment of the corporate governance mechanisms because this will reduce discretionary accrual practices by the management and in turn leads to increase earnings quality of the Nigerian listed companies.